The Conservative Processes of Palm Leaf (Bailan) Scriptures with the Participation of People in Khonkean Province - Leeka, Jaras; Pavase, PhraWandee; Katasaro, Phramahapapon; Wongpornpavan, Chakkapan; Srisaard, Wasant; Kittipanno, PhrmahaJaroon; Sirijanth, PhramahaBanjong; Promtes, Tossaporn (Journal of Buddhist Education and Research (JBER), 2015)
The Research entitled “The Conservative Processes of Bailan Scriptures (Scriptures on Palm Leaf) with the Participation of People in Khonkean Province” is of qualitative type of study. The research has three main objectives. They are: 1) To study the processes of conserving Bailan Scriptures in Khonkean Province; 2) To study the forms of the participation of people in Khonkean Province in conserving of Bailan scriptures; and 3) To study the conservation of Bailan scriptures with the participation of people in Khonkean Province. The data-analysis of this type of research has been made with the inductive methodology. The Results of research are as follows: 1. The processes of the conservation of Bailans criptures in Khonkean Province The conservation of Bailan scriptures in khon Kean province has fixed steps, that is, survey Bailan scriptures scattered in various places, collecting and dividing them into several sections for proving convenient searching, for instance, religion and philosophy, folk literatures, history and chronicle, and so on. However, the conserving of Bailan scriptures has no, in the first phase, fixed format. But, at present, after surveying, collecting and grouping them in several sections, there are many types of keeping Bailan scriptures through modern tools, for example, transmitting them from original copies to microfilms, and keeping on websites and other electronic Medias. In addition, the spreading of Bailan scriptures has been made through various ways, for instance, through giving sermon by monks on the occasion of making traditional merit, academic exhibition, conducting research, and integrating them with learning and teaching, including the spreading of knowledge from Bailan scriptures in the forms of multimedia, i.e., radio, television and website, etc. 2. The Forms of the participation of people in Khonkean province in conserving of Bailan scriptures The result of research is found that forms of participation of people in Khonkean province in conserving of Bailan scriptures have been made through cultivating awareness for the conservation of Bailan scriptures, for example, through giving correct knowledge and letting people be aware of the value of Bailan scriptures as the sources of all areas of knowledge passed down to them right now from their own ancestors. For the promotion of conserving of Bailan scriptures, it should be made with the collaboration of three important pillars of society, that is, temple, village and government office (school). Of those, there should be promotion of conserving Bailan scriptures through learning and teaching with short courses emphasized in writing and reading dhamma-script, through showcase in the learning places, and there should be academic seminars participated by monks, folk-wise persons and scholars as well. And more importantly, there should be the promotion of conserving Bailan scriptures by publishing knowledge obtained by seminar as the new set of knowledge in order to spread Bailan scriptures in various online-medias. In addition, there should be activity praising several persons and associations being able to read and write dhamma-script correctly. 3. The conservation of Bailand scriptures with the participation of people in Khon Kean Province The conservation of Bailan scriptures should have been supported budget from many organizations both government and private sector, including monks who are as the main coordinators with many organizations for fund-aid aiming at organizing activities in conserving Bailan scripture by letting all section of society to take part in supporting of fund and setting plan for conserving of Bailan scriptures, and there should have been personnel who take charge on this matter in order to make good effect to the project as well. Besides, there should have continuously been system of assessment in order to improve and develop the conservation of Bailan scriptures, and in addition to apply this result of the research for the conserving of Bailan scriptures in the future.